Pengaruh Kultur Sosial Sosial terhadap Sistem Pendidikan - Evi Rizqi Salamah (International Consortium of Education and Culture Research Studies, 2018)
This study stems from a less than optimal learning process and educational system, seen in the classroom lack of familial system when learning in the classroom. With the existence of this problem hence need of solution improvement in learning. The solution is to examine the social culture in society. The purpose of this study is to describe how the relationship between education systems in schools with existing social culture. This research uses qualitative research methods that describe things about the culture of education with the education system. Technique of collecting this data by using method of observation and interview. Based on the results of data analysis, it can be concluded that social culture is very influential on the education system. Both in the traditional era and the modern era.